The runaway heiress [large type] - Tilly, Meg (Wheeler publishing large print hardcover, 2021)
"A brave woman on the run from her vindictive husband faces a dangerous path in the thrilling new romantic suspense novel from Oscar-nominated actress Meg Tilly. Sarah Rainsford has been on the run for more than three years. She's changed identities yet again in hopes of throwing her violent estranged husband, a police lieutenant, off her trail. Since she's still legally married to him, and he is willing to bend any laws to get his hands on her inheritance, he'll stop at nothing to locate her. With a new name and fake ID papers, she lands a job as a personal assistant to none other than Hollywood's golden boy director Mick Talford. He's a difficult client but she senses hidden depths to him. Once Mick and Sarah combine forces in a desperate attempt to keep Sarah out of harm's way, they build a strong bond . . . but with danger trailing them, is it enough to keep them both alive?"--